2021
DOI: 10.1590/1807-1929/agriambi.v25n11p764-771
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soils cultivated with cassava under different managements

Abstract: Although cassava is an undemanding crop in terms of soil chemical fertility, the scarcity of nutrients affects crop productivity, and it is common to cultivate it in soils with low natural fertility, as occurs in Coastal Tablelands. In this context, the present study aimed to evaluate the physical and chemical attributes of soils cultivated with cassava under different managements. The study was carried out in the municipality of São Felipe, located in the landscape unit of Coastal Tablelands, Bahia state, Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Basic cations (Ca, Mg, K and Na) of pepper-based agroforestry land were higher than those of oneyear and fifteen years old cassava land (Table 1). Cassava cultivation in e municipality of São Felipe, Bahia state, Brazil, was reported that almost all cassava plantations had low basic cations content [12]. Leaching of basic cations, especially K and Na, was more likely to occur in the open field of cassava plantations.…”
Section: Resultsmentioning
confidence: 98%
“…Basic cations (Ca, Mg, K and Na) of pepper-based agroforestry land were higher than those of oneyear and fifteen years old cassava land (Table 1). Cassava cultivation in e municipality of São Felipe, Bahia state, Brazil, was reported that almost all cassava plantations had low basic cations content [12]. Leaching of basic cations, especially K and Na, was more likely to occur in the open field of cassava plantations.…”
Section: Resultsmentioning
confidence: 98%
“…Company X is a small and medium enterprise (SME) in the cassava industry. Cassava is a staple food crop popular for its high calorific value and its cheap source of energy (Costa et al , 2021). It has a sustained production cycle in sub-Saharan Africa due to its high levels of resilience and adaptability towards a wide range of ecological conditions (Adebayo et al , 2010).…”
Section: Case Studymentioning
confidence: 99%
“…Cow manure is preferable as the source of SOC because it is persistent until the end of the growing season (Pimentel et al, 2021). SOC level correlates positively with soil cation exchange capacity (CEC) (Costa et al, 2021), and it is able to maintain the availability of cations (Blanco-Canqui et al, 2013). This research aimed to determine the effect of SOC and NPK fertilizer levels on the growth and yield of cassava grown in ultisol soil.…”
Section: Introductionmentioning
confidence: 99%